Impact of catfish density on the waste production, water quality and mortality : Comparison between running and stagnant water system - Junaidi, M.S.; Hashida, N.H. (Agricultural Research Communication Centre, 2010)
The objective of this study was to observe the effect of African catfish, Clarias gariepinus density in stagnant and running water systems on the waste production, water quality and mortality. Nine months old male catfish having average weight of 50.00g were placed in running and stagnant water systems with density of 35 and 70, respectively. Water samples were collected twice daily and analyzed for ammonia nitrogen, phosphate and nitrate contents. The samples were analyzed with HACH spectrophotometers DR2800. Water samples temperature, pH and mortality rate were also recorded for each sampling. The results showed significant difference with higher value in stagnant than running water system for ammonia nitrogen (25.95 +/- 3.38 mg/L), phosphate (14.14 +/- 1.37 mg/L) and nitrate (2.28 +/- 0.25 mg/L) with density of 35 catfish. Similar result was obtained for density of 70 catfish which was significantly higher for stagnant than running water system. This study allow to conclude that African catfish were more suitable to be reared in running than stagnant water system. This is due to the ability of the running water system to maintain water quality in terms of waste production which was harmful to the catfish.